SÍNTESE E CARACTERIZAÇÃO DE NANOZEÓLITA A PARTIR DE RESÍDUOS (AGRO)INDUSTRIAIS PARA APLICAÇÃO EM FOTOCATÁLISE HETEROGÊNEA - Oviedo, Leandro Rodrigues (2021)
Wastewater pollution with synthetic dyes has emerged as a serious environmental problem, causing a series of deleterious effects, since they are characterized for low biodegradability and considerable chemical stability, requiring advanced treatment technologies, such as Advanced Oxidative Processes (AOPs). Among the AOPs, heterogeneous photocatalysis stands out for the use of heterogeneous nanocatalysts supported under the presence of visible light or UV radiation. In this context, this work aims to synthesize and characterize a catalytic support (nanozeolite, NZ-180) from (agro)industrial residue, evaluating the presence of metallic nanoparticles (TiNPs and AgNPs) in the Rhodamine B (RhB) dye degradation, as well as the antimicrobial activity and the nanocatalyst reuse. The samples were characterized by XRD, SEM-EDS, N2 porosimetry, DLS, FTIR and zeta potential. The antibacterial activity was carried out using the minimal inhibitory concentration (MIC) against 4 bacterial strains (K. pneumoniae, S. aureus, P. aeruginosa and E. coli). The central composite rotational design (CCRD 2²) was carried out to determine the ideal condition for the photocatalytic process. XRD diffractograms patterns indicated the presence of characteristic pure phase peaks of analcime for NZ-180, as well as anatase and rutile (TiNPs@NZ-180) and Ag2O (AgNPs@NZ-180) phases. Moreover, nanomaterials showed mesoporous characteristics, with a specific surface area between 35.9 - 418.0 m² g-1, pore diameter between 13.01 - 18.5 nm and pore volume between 0.076 - 0.092 cm³ g-1, besides the presence of stretching of Al-O, Si-O, TiO-O, Ag-O, Ti-O and AgO-O. All samples had negative charges (between -14.65 and -29.69 mV) and a regular spherical structure morphological. About the photocatalytic tests, TiNPs@NZ-180 showed the best photocatalytic activity (around 62.26 and 50.82% degradation under UV radiation and visible irradiation, respectively), with the ability to be reused in 5 photocatalytic cycles, resulting in a reduction of about 10% in the activity. The ideal conditions determined by the CCRD were [NZ-180] = 2.75 g L-1 and [RhB] = 20 mg L-1. AgNPs@NZ-180 showed antibacterial activity against all bacterial strains tested, resulting in a MIC value equal to 250 μg mL-1. Therefore, it was possible to synthesize heterogeneous supported nanocatalysts from (agro)industrial residues with potential properties for application in wastewater removal, with antimicrobial activity, meeting the theme of sustainable development with nanotechnology.